2004
DOI: 10.1002/pssb.200301947
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nonlinear optical parameters of copper‐ and silver‐doped silica glasses at λ = 1064 nm

Abstract: Investigations of nonlinear optical characteristics (nonlinear refractive indices, nonlinear absorption coefficients and third-order nonlinear susceptibilities) of copper and silver nanoparticles implanted in glasses are presented using picosecond Nd : YAG laser radiation (λ = 1064 nm) and the Z-scan technique. The variations of the sign of the nonlinear refractive indices depending on matrix properties are analyzed. It is shown that the nonlinear absorption in copper-doped glasses is due to the two-photon eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Metal nanoparticle systems like metal-doped glasses or colloidal solutions are of considerable interest due to fast response time on laser excitation [1,2] and large value of the third-order nonlinear susceptibility, w (3) , responsible for Kerr effect [3][4][5][6]. Optical nonlinearities of gold nanoparticles were the subject of numbers of investigations during the past decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal nanoparticle systems like metal-doped glasses or colloidal solutions are of considerable interest due to fast response time on laser excitation [1,2] and large value of the third-order nonlinear susceptibility, w (3) , responsible for Kerr effect [3][4][5][6]. Optical nonlinearities of gold nanoparticles were the subject of numbers of investigations during the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…The role of surrounding matrix characteristics was also the subject of numerous studies. Thus, for example, water [7][8][9][10], silicate glass [3][4][5], BaTiO 3 [11], Al 2 O 3 [12,13], LiNbO 3 [14], TiO 2 [15] were applied for composite material optimization to obtain appropriate values of the nonlinear optical coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that, in numerous studies, the transition from the saturable effect to the reverse-saturable effect was observed with increased light intensity [7,9,[16][17][18][19][20]. However, usually, high optical power density was necessary to achieve such a change.…”
Section: Introductionmentioning
confidence: 99%
“…Annealing in Ar at 500-900C, 1 h. Ishikawa et al, 2002, Tsuji et al 2002a, 2002b, 2003a, 2005a, 2005b, Arai et al, 2003 SiO 2 , 1998, 1999a, 1999b, 1999c, 2000a, 2000b, 2000c, 2001a, 2001b, 2001c, 2002b, 2002c, 2002b, 2003a, 2003b, 2003c, 2004a,2005b, 2008a, 2008b, 2009aHole et al 1999Ganeev at al. 2003a, 2003b,2004a, 2004c The range of high-dose implantation may be divided into two characteristic dose subranges. In the range 10 15 ≤ ~F 0 ≤ 10 17 ion/cm 2 , the concentration of Ag ions exceeds the solubility limit of metal atoms in matrices and the system relaxes by nucleation and growth of MNPs (Fig.…”
Section: Ion Synthesis Of Metal Nanoparticlesmentioning
confidence: 99%